TUMOR PREVENTIVE POTENTIAL OF CROMOLYN IN 7, 12-DIMETHYLBENZ(A)ANTHRACENE INDUCED HAMSTER BUCCAL POUCH CARCINOGENESIS - SEKAR KARTHIKEYAN,; SHANMUGAM MANOHARAN, (International Journal of Pharma and Bio Sciences, 2016)
Cromolyn explored diverse pharmacological effects including antioxidant, anti-inflammatory and anticancer properties. The cytotoxic or anti-cell proliferative potential of cromolyn has been well documented in various cancer cell lines. To date, there are no studies on the chemopreventive potential of cromolyn against 7,12-dimethylbenz(a)anthracene (DMBA) induced oral carcinogenesis. The chemopreventive efficacy of the cromolyn was substantied with the incidence of tumor formation, histological abnormalities and by analysing the status of biochemical markers such as lipid peroxidation by products, antioxidants and phase I and II detoxification agents in DMBA induced hamster buccal pouch carcinogenesis. Well differentiated squamous cell carcinoma was noticed in the buccal pouches of hamsters treated with DMBA (three times a week for 14 weeks). Cromolyn completely prevented the tumor formation and restored the status of biochemical markers in the pre-initiation phase. Also cromolyn reduced the tumor size and burden as well as improved the status of biochemical markers in the post-initiation phase. The present results thus implicate the tumor preventive potential of cromolyn in DMBA induced hamster buccal pouch carcinogenesis.